Relation of Nanostructure and Recombination Dynamics in a Low‐Temperature Solution‐Processed CuInS2 Nanocrystalline Solar Cell. Issue 12 (1st August 2013) - Azimi, Hamed; Heumüller, Thomas; Gerl, Andreas; Matt, Gebhard; Kubis, Peter; Distaso, Monica; Ahmad, Rameez; Akdas, Tugce; Richter, Moses; Peukert, Wolfgang; Brabec, Christoph J.
<x xml:space="preserve">Abstract</x> The understanding and control of nanostructures with regard to transport and recombination mechanisms is of key importance in the optimization of the power conversion efficiency (PCE) of solar cells based on inorganic nanocrystals. Here, the transport properties of solution‐processed solar cells are investigated using photo‐CELIV (photogenerated charge carrier extraction by linearly increasing voltage) and transient photovoltage techniques; the solar cells are prepared by an in‐situ formation of CuInS2 nanocrystals (CIS NCs) at the low temperature of 270 °C. Structural and morphological analyses reveal the presence of a metastable CuIn5S8 phase and a disordered morphology in the CuInS2 nanocrytalline films consisting of polycrystalline grains at the nanoscale range. Consistent with the disordered morphology of the CIS NC thin films, the CIS NC devices are characterized by a low carrier mobility. The carrier density dynamic indicates that the recombination kinetics in these devices follows the dispersive bimolecular recombination model and does not fully behave in a diffusion‐controlled manner, as expected by Langevin‐type recombination. The mobility–lifetime product of the charge carriers properly explains the performance of the thin (200 nm) CIS NC solar cell with a high fill‐factor of 64% and a PCE of over 3.5%.